Laparoscopic Cholecystectomy for Acute Calcular Cholecystitis in a Patient with Ventriculoperitoneal Shunt: A Case Report and Literature Review - Abdullah A. Albarrak; Sami Khairy; Alzahrani Mohammed Ahmed (Case Reports in Surgery)
Management of patients who have ventriculoperitoneal shunt presenting with acute calcular cholecystitis has remained a clinical challenge. In this paper, the hospital course and the follow-up of a patient presenting with acute calcular cholecystitis and ventriculoperitoneal shunt managed with laparoscopic cholecystectomy are presented followed by literature review on the management of acute calcular cholecystitis in patients who have ventriculoperitoneal shunts.